The Reforming Of Money Politics Cases In Election Law As Corruption Crime - Wawan Setiyawan; Anis Mashdurohatun (Universitas Islam Sultan Agung, 2021)
This research aims to knowing and analyzing the reformulation of money politics in the election law as a criminal act of corruption. The research method in writing this journal uses normative (doctrinal) research methods. Based on the research, it is concluded that reformulation of money politics in the election law as a corruption crime can be done by including a clause on political corruption as a special offense in the General Election Law so that it can be a strong legal basis for law enforcement officials to take steps - preventive or repressive measures to realize clean elections and corruption-free politics.